Molps: uma ontologia para definição de linha de produto de software para gerência de projeto com metodologias ágeis - Lermen, Michele (Universidade do Vale do Rio dos Sinos, 2012)
This study aims to develop an ontology to represents a software product line to be used for project management based on agile methodologies. The product line domain model was built utilizing concepts coming from eXtreme Programming (XP), Scrum, and feature driven development (FDD), and also concepts brought from project management through PMBOK. Through the ontology Molps proposes to represent this domain, enabling software agents to perform queries on the ontology, inferring the possible variability in the product to be generated. The ontology will also allow the management process of software development. To demonstrate this flexibility and process management software development take place in the ontology developed tests, where results are discussed and analyzed.
Keywords: Metodologias ágeis; Gerenciamento de projetos; Linha de produto de software; Ontologias; Agile methodologies; Project management; Software product line; Ontology; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação